(untitled) (European Journal of Pure and Applied Mathematics, 2020)
The aim of this paper is to establish new common fixed point results for multivalued integral type contraction mappings on a family of sets endowed with a graph. The obtained results generalize several recent ones. An example of application is included to illustrate the main existence theorem.